A few days ago
carol ellen

# Algebra question; solve this equation 2x squared -x=3. Factor this problem. Can anyone help me?

Algebra question; solve this equation 2x squared -x=3. Factor this problem. Can anyone help me?

A few days ago
dohboy000

2x^2-x=3

subtract 3

2x^2-x-3 = 0

factor

(2x-3)(x+1)=0

that means either 2x-3 = 0 or x+1=0

so x =3/2 or x = -1

0

A few days ago
Anonymous
(x+1)(2x-3)

don’t ask me how i got it, it’s right.

okay, fine, here’s the work:

subtract three to the other side so that you have all the numbers on the left side equaling zero. next you use this method where you multiply 2x squared by 3 (the first and last times each other) you get -6. then you figure out what multiplies to negative six and adds to -1 (because the middle term is -x which is also known as -1x). the answer for that is -3 and 2. next you factor it out. you end up with

x(2x-3) + 1(2x-3). you factor a little more and end up with (x+1)(2x-3)

Here are the steps with the math and the numbers:

2x^2 – x = 3

2x^2 – x – 3 = 0

2x^2 – 3x + 2x – 3 = 0

x(2x-3) + 1 (2x-3)

(x+1)(2x-3)

hope that helps and made a little bit of sense. if it didn’t, well, i can assure you that that answer is right. you can trust me.

0

A few days ago
WaterfallOfDestiny
2x^2-x = 3

Moving all of the terms to one side, we get: 2x^2-x-3=0

From there, we can factor to solve for x: (2x-3)(x+1)=0

Any number multiplied by 0 equals 0, so:

2x-3=0 or x+1=0

Isolating x to get our final answer, we get:

x=3/2 or x=-1

0

A few days ago
Anonymous
2xsquared -x =3

2x squared -x -3 =0

(2x -3)(x +1) = 0

0

A few days ago
tom4bucs
first – let’s get everybody on the same side = 0

so – subtract 3 from both sides….yields

2x^2 – x -3 = 0

2 factors (1,2) and 3 factors (1,3)

NOW – since BOTH are minuses – one will be positive and the LARGER will be the minus

(2x-3)(x+1) = 0

all the best !

0

A few days ago
?
2x^2 – x – 3 = 0

(2x -3) (x+1) = 0

0